The Construction of an Optimal balanced Fund Consisting Indonesian Stock and Bonds (Case Study: LQ45 Stocks and Government Bonds as of July 2009 - June 2014) - Lontoh, Adellia Debyane; Anggono, Achmad Herlanto (Journal of Business and Management, 2014)
This study concerns about the optimization construction of a balanced fund consisting the LQ45 stocks and Indonesian Government Bonds, which also includes the assessment of each single asset risk-return tradeoff and the performance measurement of the constructed optimal balanced fund portfolio. The time scope of this study ranges as of 1 July 2009 to 30 June 2014. Several data required to conduct the analysis of this study that include the historical daily price of stocks, bonds, Jakarta Composite Index, and LQ45, as well as the monthly data of BI Rate as the risk-free rate used in this study. The selected stocks and bonds were further analyzed in the asset allocation as a part of the portfolio optimization, by attaining the possible maximum return at a given risk and the possible minimum variance at a given expected return, as refers to the Mean-Variance analysis in Markowitz Portfolio Theory. The Efficient Frontier was also constructed to ensure that the constructed portfolios lie in the Efficient Frontier. The constructed balanced fund was ultimately selected based on the 3 (three) measurement indices. The selected balanced fund was assessed to perform above the markets regarding its high return, Sharpe Ratio, and Treynor Index, as well as low standard deviation as below the JCI and LQ45, and Alpha that positively identified above the markets. The author believes this study may ensure readers to invest in balanced fund that provides minimum risk for certain return with high excess return.Keywords: Balanced Fund, Portfolio, Optimization, LQ45 Index, Stocks, Indonesian Government Bonds, Jakarta Composite Index, BI Rate, Mutual Fund, Markowitz Portfolio Theory